Design Analysis of Flexible and Rigid Pavements For The Sampang-Ketapang Road (Link 113): A Cost and Time Perspective - Muhammad Zainal Muttaqin; Esti Wulandari; Laksono Djoko Nugroho (Journal of Social Research, 2025)
This study evaluates the costs and implementation times for flexible and rigid pavement designs for the Sampang-Ketapang road (Link 113) using the 2024 Pavement Design Manual. The flexible pavement design, using Class A aggregate with a thickness of 200 mm, costs IDR 12,804,591,492 and requires a 7-month implementation period. In contrast, the rigid pavement design, with 300 mm concrete and a flexural strength of 4.5 MPa, costs IDR 19,513,787,534 and takes 9 months to complete. While flexible pavement is more cost-efficient and quicker to implement, making it suitable for projects with budget and time constraints, rigid pavement offers greater durability and reduced maintenance over time, which may justify its higher initial cost for roads with heavy traffic. This study emphasizes the importance of selecting the appropriate pavement type based on traffic conditions, subgrade characteristics, and budget limitations. Flexible pavement is recommended for segments with moderate traffic and short-term construction needs, while rigid pavement is better suited for high-traffic areas requiring long-term durability. The research suggests a strategic combination of both pavement types to optimize cost and efficiency while ensuring sustainability. The findings provide practical guidance for stakeholders in road infrastructure projects, offering a framework to balance initial costs, construction timelines, and long-term maintenance to achieve optimal outcomes in road widening projects like the Sampang-Ketapang road expansion.